Construction and validation of a technical-tactical performance evaluation instrument in volleyball. DOI: 10.5007/1980-0037.2011v13n1p43 - Joice Mara Facco Stefanello; Juarez Vieira do Nascimento; Valmor Ramos; Carine Collet (Universidade Federal de Santa Catarina, 2011)
The aim of this study was to develop and validate a technical-tactical performance evaluation instrument in volleyball (PEI-VB). Observation indicators were constructed based on the literature and on already established evaluation models. Content validation was performed by 10 experts in the field for the dimensions of clarity of language, practical relevance and theoretical relevance. Intra-examiner (test-retest method) and inter-examiner (6 examiners) reliability was tested. Data collection consisted of the analysis of a video of games from the finalist team of the 2009 Catarinense Children's Volleyball Championship. Data were analyzed using the SPSS for Windows 11.5 and SAS programs, with the level of significance set at 5%. Spearman's correlation coefficient, weighted kappa index of agreement, and intraclass correlation coefficient were used for the analysis of each specific action of the game and each performance component. The PEI-VB comprises an instrument that evaluates the components of technical-tactical performance of the actions of a 6x6 volleyball game, permitting the identification of the general performance level of each player, as well as the specific performance according to action and component. In addition, the validity of the instrument was 92.9% and the intra- and inter-examiner reliability was 0.84 and 0.78, respectively. All indices were high, indicating that the PEI-VB is a valid and consistent instrument that permits the evaluation of the level of sports performance of volleyball players of different categories.